2000
DOI: 10.1029/2000jd900086
|View full text |Cite
|
Sign up to set email alerts
|

Observations of new particle production in the atmosphere of a moderately polluted site in eastern England

Abstract: Abstract. Measurements of particle number density and Fuchs surface area, together with a range of gaseous pollutant concentrations, have been made in June 1995 at a coastal site in eastern England which receives air from a range of polluted and less polluted origins. Periods of enhanced local particle production were identified and found to be associated predominantly with relatively polluted air sectors. An examination of the factors contributing to homogeneous nucleation and hence new particle production su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Secondly, we used a so-called timeshift analysis, which compared the shape of two curves -sulphuric acid and the particle number concentration between 3 and 6 nm (N3 hereafter). A similar analysis has been used by Weber et al (1997) and Harrison et al (2000). In Fig.…”
Section: Growth Ratesmentioning
confidence: 87%
“…Secondly, we used a so-called timeshift analysis, which compared the shape of two curves -sulphuric acid and the particle number concentration between 3 and 6 nm (N3 hereafter). A similar analysis has been used by Weber et al (1997) and Harrison et al (2000). In Fig.…”
Section: Growth Ratesmentioning
confidence: 87%
“…These studies concluded that photochemistry is a governing process which involves formation of the hydroxyl radical (Harrison et al, 2000) and thus produces the nucleating and/or condensing species for the new particle formation and subsequent growth. Fig.…”
Section: Effect Of Meteorological Parameters On Particle Growthmentioning
confidence: 99%
“…in Mexico City (Dunn et al, 2004), in lower Fraser Valley (Mozurkewich et al, 2004), in eastern England (Harrison et al, 2000), in Athens, Greece, Marseille, France and New Delhi, India , in Milan, Italy (Baltensperger et al, 2002) and in Atlanta, Georgia (McMurry et al, 2005). These measurements have mainly been short term but also longer data series have been recorded in urban locations, including Atlanta, Georgia for 13 months (Woo et al, 2001), Birmingham, UK for one year (Alam et al, 2003), St. Louis, Missouri for one year (Shi and Qian, 2003), Pittsburgh, Pennsylvania for about one year (Stanier et al, 2004a, b), Beijing, China for one year (Wu et al, 2007) and Fresno Supersite, Central California, for almost two years (Watson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%